Is China's Export-Oriented Growth Sustainable? - Guo, Kai (IMF Working Papers; Working Paper ;, 2009)
This paper assesses the sustainability of China's export-oriented growth over the medium to longer term. It shows that maintaining the current export-oriented growth would require significant gains in market share through lower prices in a range of industries. This, in turn, could be achieved through a combination of increases in productivity, lower profits, and higher implicit or explicit subsidies to industry. However, the evidence suggest that it will prove difficult to accommodate such price reductions within existing profit margins or through productivity gains. Moving up the value-added chain, shifting the composition of exports, diversifying the export base, and increasing domestic value added of exports could give room to further export expansion. However, experiences from Asian economies that had similar export-oriented growth suggest there are limits to the global market share a country can occupy. Rebalancing growth toward private consumption would provide a large impetus to output growth and reduce the need for gaining further market share.